Humanising Through Conjecture: Recognition and Social Critique among Houseless People. - Schneider, Luisa T. (Ethnos: Journal of Anthropology, 2024)
There are aspects of fieldwork which elude our ethnographic toolkit. How can we, for instance, theorise on mental illness and addiction among the houseless without pathologising or medicalising? Based on 3½ years of fieldwork this article argues for a speculative approach that interweaves critical phenomenology, compassionate storytelling and analytical autoethnography. It reflects on a rough sleeper who kept asking me 'Are you laughing at me?' thereby revealing a process of mutual de-individualisation and re-individualisation. By producing moments of confrontation where subconscious presumptions no longer work, people issue critique of the routinised violence they are subject to, negotiate their fears and desires and seek recognition. Using micro-moments to investigate larger structural processes and questions of power, identity and belonging, the contribution of speculative anthropology lies in humanising. Combining deep ethnographic insights with projection and conjuncture offers avenues for decentring and for doing and interpreting anthropology compassionately, critically, and equivocally.